Contact Cooling dan Hubungan Material Lantai, Alas Lantai, dan Kondisi Termal Ruangan Unit Hunian Rusun Sewa di Surabaya - Graciani Cahyadresta Dewanda; Sri Nastiti Nugrahani Ekasiwi; I Gusti Ngurah Antaryama (Universitas Udayana, 2024)
This study examines the significant role of the floor in contact cooling, which is passive cooling that happens through direct contact with the human body. It investigates the dynamic of the relationship between floor covering materials, mats, and thermal conditions, a topic that has not been widely explored. As a starting point, this study correlates thermal conditions and the use of mats in three highrise rental flats in Surabaya. Study results show that floor temperature tends to be higher than room temperature. The average room temperature is 30.61°C, while the floor temperature reaches 32.20°C on average. The widely used underlay material is polypropylene carpet with an average thickness of 4.23±4.99 mm. In the context of a contact cooling process, floor covering materials act as both radiative and conductive cooling elements. Meanwhile, mats act as a thermal moderation whose condition can be adapted to match the occupants' behavioral patterns and preferences.Keywords: thermal condition; floor covering material; contact cooling; rental highrise unit AbstrakStudi ini mendalami peran signifikan dari lantai dalam contact cooling - pendinginan pasif yang terjadi melalui sentuhan langsung dengan tubuh manusia. Studi menginvestigasi dinamika dari hubungan antara lantai, alas lantai, dan kondisi termal, sebuah topik yang belum dieksplorasi secara luas. Sebagai titik awal, studi ini mengkorelasikan kondisi termal dengan pemanfaatan alas lantai di hunian rusun sewa di Surabaya. Hasil penelitian menunjukkan bahwa suhu lantai cenderung lebih tinggi daripada suhu ruangan. Rata-rata suhu ruangan adalah 30.61°C, dan rata-rata suhu lantai adalah 32.20°C. Jenis material alas yang banyak digunakan adalah karpet polypropylene dengan ketebalan rata-rata adalah 4.23±4.99 mm. Dalam konteks contact cooling, lantai berperan sebagai elemen radiative dan conductive cooling. Sedangkan alas berperan sebagai moderasi termal yang bisa diadaptasikan sesuai dengan patrun tingkah laku dan preferensi dari penghuni.Kata kunci: kondisi termal; bahan penutup lantai; contact cooling; rusun sewa